Metodologia de análise do colapso de tensão em tempo real considerando limites de potência ativa e reativa de geradores - Justi, Alyne Nogueira (2017)
Due to the high energy demand and the high complexity of today's interconnected Electrical Power Systems (SEPs), it is becoming increasingly important for the system operator to know the current state of the SEP. In addition, have the tools to predict situations that may compromise the smooth operation of the system. As a good operation, the continuity of the supply and adequate voltage profiles are correct, even after the occurrence of disturbances, which can be affected by the phenomenon of voltage instability (or voltage collapse). Therefore, the objective of this work is to develop a methodology for the analysis of voltage collapse in real time considering the limits of active and reactive power of generators, which aims to assist the system operator. This methodology is divided into five steps. The first one consists of an analysis of the base case of the considered SEPs, using an algorithm that allows estimating the voltage stability margin of the system considering the limits of active and reactive power of the generators. This first step uses the continuous power flow methodology, using load and voltage as continuation parameters. The second stage presents a fast contingency analysis considering simple contingencies of transmission lines, following the criterion N-1. In this second step, the Modified Look Ahead method was used. The third step is an accurate analysis of the most critical contingencies, identified in step two, in order to verify the presence of limits-induced bifurcations. In this third step, we also used the continuous power flow methodology. In the fourth step, all available system controls, such as capacitor bank insertion and TAP adjustment of the transformers, are applied in order to verify the impact of these control actions on the safe operation limit of the system, using the Look Ahead Modified. These four steps enable a real-time analysis of the voltage stability of the system. Finally, a fifth stage of analysis of Offline contingencies is proposed, and a more precise analysis of all the contingencies using the methodology of continuous power flow is proposed. The SEPs analyzed in this dissertation were the Stagg five-bar system, the Institute of Electrical and Electronics Engineers (IEEE) standard fourteen bar system and the IEEE standard thirty-bar system.